Cromatografía líquida aplicada a análisis de alimentos - Vela Tuanama, Danisca Frangoysi (Universidad Nacional de la Amazonía Peruana, 2022)
High-performance liquid chromatography or HPLC is one of the analysis procedures for all types of materials, including food, and is currently the most widely used procedures today, thanks to the fact that it uses techniques that were previously not accessible, such as adsorption, division, molecular exclusion and affinity chromatography. This work reveals the basic principles of the method and the ways in which the division and/or study of the applied sample in food analysis can be successfully approached.

La cromatografía líquida de alto resolución o HPLC es uno de procedimientos de análisis de todo tipo de materiales entre ellos los alimentos y el más utilizado en la actualidad, gracias a que emplea técnicas que previamente no estaban accesibles, como las cromatografías de adsorción, partición, exclusión molecular y afinidad. Este trabajo da a conocer los principios básicos del método y las formas como se puede abordar de forma exitosa la división y/o estudio de la muestra aplicada en análisis de alimentos.
Keywords: Procedimientos; Análisis de alimentos; Cromatografía; https://purl.org/pe-repo/ocde/ford#2.04.01